2021
DOI: 10.3390/molecules27010218
|View full text |Cite
|
Sign up to set email alerts
|

Panos-Fermented Extract-Mediated Nanoemulsion: Preparation, Characterization, and In Vitro Anti-Inflammatory Effects on RAW 264.7 Cells

Abstract: This study focused on developing Panos nanoemulsion (P-NE) and enhancing the anti-inflammatory efficacy for the treatment of inflammation. The effects of P-NE were evaluated in terms of Nitric oxide (NO production) in Lipopolysaccharide (LPS), induced RAW 264.7 cells, Reactive oxygen species (ROS) generation using Human Keratinocyte cells (HaCaT), and quantitative polymerase chain reaction (qPCR) analysis. Sea buckthorn oil, Tween 80, and span 80 were used and optimize the process. Panos extract (P-Ext) was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The study revealed that Panax ginseng, which is known as the king of medicinal plants, successfully formed NE with sea buckwheat fruit oil. That study also demonstrated the inhibition of pro-inflammatory mediators in vitro compared to Panax ginseng alone [79,80]. Previously, an in vivo study in a mouse ear model with curcumin NE (formed with MCT) from the Curcuma longa medicinal plant focused on the inhibition effects of edema as an anti-inflammatory potential [81].…”
Section: Plant-based Nanoemulsion For Inflammationmentioning
confidence: 73%
“…The study revealed that Panax ginseng, which is known as the king of medicinal plants, successfully formed NE with sea buckwheat fruit oil. That study also demonstrated the inhibition of pro-inflammatory mediators in vitro compared to Panax ginseng alone [79,80]. Previously, an in vivo study in a mouse ear model with curcumin NE (formed with MCT) from the Curcuma longa medicinal plant focused on the inhibition effects of edema as an anti-inflammatory potential [81].…”
Section: Plant-based Nanoemulsion For Inflammationmentioning
confidence: 73%